Determinant of Nokia's Users Loyalties (Case Study on Societies of Air Simpang Village, Ketahun Subdistrict, Bengkulu Utara) - Andi Azhar; Novilia Novilia (Faculty of Economic and Business, 2016)
This study aimed to analyze the impact of the quality and price perception to the loyalty of Nokia mobile phone users in the Air Simpang Village. Ketahun Subdistrict, Bengkulu Utara. The primary data used in this study was obtained from a questionnaire distributed to 318 people who meet the criteria respondent sample. The results showed that the quality of the product has positive effect on customer loyalty, and price has a positive effect on customer loyalty. Based on regression testing, the independent variable that most influence on customer loyalty of mobile phone users in the Water Village Simpang is the price.DOI: 10.15408/etk.v15i1.2837